THE EFFICACY OF THE COSTS ON SEVERE RESPIRATORY SYNCYTIAL INFECTION PREVENTION WITH PALIVIZUMAB IN PRETERM INFANTS - A. V. Rudakova; I. V. Babachenko; V. B. Rovnyi; A. N. Uskov; Yu. V. Lobzin (Вопросы современной педиатрии, 2012)
Respiratory syncytial virus plays a significant role in etiology of respiratory infections in infants, and preterm children have muchhigher risk of severe course of the disease, than common population of children at the age less than 2 years old. Palivizumab is usedefficiently to prevent this infection. The aim of this study was to assess the efficacy of the costs on palivizumab in preterm childrenin the Russian Federation. The assessment was based on meta-analysis of randomized clinical trials. According to the World Health organization recommendations, the acceptable value of the variable «costs/efficacy» must not be higher than threefold of the gross domestic product per person. On the assumption of this fact, the coefficient «costs/efficacy» for the Russian Federation according to the 2011 year results must not be higher than 1140 thousand rubles per 1 extra year of life. Analysis from the position of health care system shows, that coefficient «costs/efficacy» with palivazumab usage in children with gestation age from 28 to 32 weeks rangesfrom 594,4 to 1030,4 thousand roubles per 1 extra year of life when starting the prophylaxis during first 6 month of life. Under the social perspective of the study (accounting for direct and indirect costs) the coefficient «costs/efficacy» decreases to 515,8–951,8 thousands roubles per 1 extra year of life. Thereby, nowadays the prophylaxis of severe respiratory cyncytial infection with palivazumab is acceptable according to the economical point of view in preterm children with the gestation age 32 weeks and less when starting during first 6 months of life.